Virtual Restoration of Faces Appearing in Byzantine Icons - Voutounos, Chrysanthos; Stylianou, Georgios; Lanitis, Andreas (My University, 2012)
Virtual restoration of cultural heritage (CH) artefacts is an important task that aims to digitally recreate the original appearance of damaged items. In this paper, a method that can be used for virtual restoration of faces appearing in damaged Byzantine icons is presented. Given a damaged face, the complete three-dimensional (3D) geometry of the face is reconstructed using data from the non-damaged facial parts and the texture of the damaged areas is restored. A key aspect of the proposed method is the use of a customized 3D deformable face model suitable for representing the geometry of Byzantine faces, the so-called Byzantine Style Specific Model (BSSM). A BSSM is generated by enforcing rule-based constraints on a deformable model trained using 3D scans of human faces. The use of a BSSM ensures that the Byzantine style is preserved during the process of shape restoration.
Keywords: Icons, Byzantine; Virtual work